Four Criteria for Labeling Black Women and Their Community as 'Others' in Toni Morrison's Novels - Sri Herminingrum (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
The dynamics of Black women's life, from Slavery Era to Women Rights Movement in 1980-s, highlighted by Morrison in The Bluest Eyes, Sula, Song of Solomon, Tar Baby, Beloved, Jazz, Paradise, and Love is cultural expression which is in a non-exclusive territory. By applying interdisciplinary approach - integrating theories and perspectives of some disciplines, including the intersectional zone of the study of gender, sexuality, race, and ethnicity - to research these eight novels, it was discovered that there are four points engendering Black women regarded as 'other'. (1) Mother-centered culture practice. (2) Double lives for racism and sexim. (3) The impact of White culture invasion. (4) The struggle for building self dignity.